A case for FPGA-based accelerators for energy-efficient motion picture video processing - Shanker, Shreejith (SPIE, 2023)
In recent years, computing-based video processing workflows have become an integral part of the motion picture industry. These workloads are highly data- and compute-intensive, requiring capable hardware to achieve the required performance. Currently, general-purpose CPUs and GPUs are used to accelerate video processing functions in motion picture workflows. While such devices are highly suited to software-driven video processing workflows, they consume large amounts of energy in these tasks. In this work, we present a case for deploying an FPGA-based accelerator as an energy-efficient alternative to general-purpose hardware in high-resolution motion picture video processing, using an ingest module as a case study. We show that an FPGA-based accelerator for decoding 8K OpenEXR B44 video frames, designed using a commercial high-level synthesis workflow and executing on a PCIe-connected Alveo U50 device, outperforms a highly parallel, CPU-optimised inbuilt B44 decoder implementation in terms of energy consumption per frame decoded. In our experiments, the FPGAaccelerated B44 was able to decode 8K frames with 47.9 ms latency while consuming 0.98 J of energy per frame, compared to the 58.3 ms achieved by a high-end Intel 11700-K CPU while consuming 4.5 J per frame, when averaged over 1000 runs. We further show that this offload can be seamlessly integrated into state-of-the-art motion picture tools such as NUKE with minimal effort. With FPGAs becoming mainstream in cloud servers, we envision that this work paves the way for more efficient integration and utilisation of custom hardware and FPGAs in compute-intensive motion picture workflows.
Applications of Digital Image Processing XLVI
PUBLISHED
San Diego
Keywords: Field-programmable gate arrays; Energy-efficient processing; Hardware-accelerators; High-performance computing; Motion pictures; Video processing; Digital Engagement; Making Ireland; Smart & Sustainable Planet; Engineering Design; Field Programmable Gate Arrays (FPGAs); Image Processing; Reconfigurable Computing; Signal processing; VIDEO PROCESSING